Transcranial magnetic stimulation to reduce suicidality – A review and naturalistic outcomes. (June 2020) - Bozzay, Melanie L.; Primack, Jennifer; Barredo, Jennifer; Philip, Noah S.
Abstract: Although there is growing interest in the use of repetitive Transcranial Magnetic Stimulation (TMS) as a treatment for suicidality, efficacy data in this area, and knowledge of potential treatment mechanisms, remains limited. The first objective of this study was to systematically review clinical trial data examining the effectiveness of TMS as a treatment for suicidal ideation. Our secondary objective was to investigate the extent to which changes in suicidality are independent of improvements in depression in a clinical sample of veterans who received TMS treatment. In Study 1, we searched the Pubmed and biRxiv databases from inception until July 2019 to identify studies that examined the efficacy of TMS for suicidal thoughts and/or behaviors. Data regarding sample characteristics, treatment parameters, and results were synthesized from six randomized controlled trials and five unblinded trials (total n  = 593). Our systematic review indicated that while TMS was consistently associated with reduced depression, its impact on suicidality is unclear. Interpretation of results related to suicidality were complicated by study design elements and modest sample sizes. In Study 2, we conducted a retrospective analysis of 43 patients who received care for depression in a neuromodulation clinic at a Veteran's Affairs hospital. Results found significant decreases in suicidal ideation, and depressive symptom change did not always account for improvements in ideation. Taken together, our literature review and clinic study indicate preliminary promise of TMS for suicide, and underscore the need for more fine-grained, suicide-specific TMS research.